NEXT-GEN AI FOR BUSINESS TRANSFORMATION - Meepung, Tippawan (RMUTT Global Business and Economics Review, 2025)
This academic paper examines the process of transforming business to modern era with artificial intelligence technology. To serve as a guide for digital entrepreneurs in Thailand. Referring to information from global indices and government policies that support the creation of artificial intelligence innovation for the public and private sectors. Business transformation involves many factors, including the integration of advanced technologies into business processes. Adapting new business strategies and models Developing skills in using artificial intelligence for personnel, determining operational measures. Reorganization and culture evolution. The business transition to the artificial intelligence era with agentic AI is an evolution of AI that could understand commands or targets and turn them into a series of complex actions without relying on human control. It is considered a change in AI that supports entrepreneurs in the digital era for competition. The Artificial Intelligence regulatory framework under the EU AI Act and the National AI Action Plan for Thailand’s Development establishes guidelines for data management to associate technology, ethics, and good governance, build consumer confidence, and promote social responsibility.